2000
DOI: 10.1080/03067310008034132
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Carbonyls in Large Midwestern Office Buildings

Abstract: Airborne carbonyls in large office buildings in the Midwestern United States have been studied both indoors and near the air-intakes environment using HPLC and GCMS methods. Air sampling for carbonyls was conducted using 2.4-dinitrophenylhydrazine coated silica gel cartridges and stainless steel Tenax TAB tubes. 1,3-dinitrobenzene, 2.4-dinitrophenol and 2.4-dinitroaniline were tentatively identified as degradation products of 2.4-dinitrophenylhydrazine by HPLC and GCMS analysis. Performance of the Tenax TAB-GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Some industrial processes have aldehydes as one of the raw materials and emissions may take place both in the manufacturing process and from use of the products. It has been reported that aldehyde emissions from building material are affecting indoor air quality [6][7][8][9][10]. Natural emissions of aldehydes from vegetation have also been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Some industrial processes have aldehydes as one of the raw materials and emissions may take place both in the manufacturing process and from use of the products. It has been reported that aldehyde emissions from building material are affecting indoor air quality [6][7][8][9][10]. Natural emissions of aldehydes from vegetation have also been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…(17)(18)(19) This paper comprehensively presents the methods used for this study and summarizes results from the rst round of sampling in each building (November 1996 to April 1997).…”
mentioning
confidence: 99%
“…Therefore, the investigation of the α-dicarbonyl sources is very necessary for the protection of human health. There have been extensive researches on carbonyl compounds in the indoor environment (Baez et al 2003;Dassonville et al 2009;Ohura et al 2006;Santarsiero and Fuselli 2008;Sax et al 2004;Subramanian et al 2000). However, there has been a lack of research on indoor α-dicarbonyl (Liu et al 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%